ALASAN PEMILIK TENDA BIRU MEMPERTAHANKAN USAHANYA DI KELURAHAN OLO KOTO MARAPAK PADANG BARAT - Karwiza, Yulasmi - (Pendidikan Sosiologi, 2014)
Yulasmi Karwiza, (10,070,106). Reason owners Tenda Biru Maintain His efforts in the Village Olo Marapak Koto Padang West. Thesis. Sociology of Education Studies Program, School of Teacher Training and Education (STKIP) PGRI West Sumatra, Padang, 2014. The background of this research effort with theb lue awningis often held by amunicipal police raidin the village of Olo Koto Padang Marapak West. Associated with the reality on the ground that the owner of a blue tent open blue awning has violated the existing rules, but in fact the owner of the blue awning still retaining their business. This study aimed to describe the reason for the owner of a blue tentin the village of Olo Marapak Koto Padang West.The theory used in this study is phenomenology by Alfred Schutz, 1998:129. This type of research is qualitative research. Research informants taken purposive sampling. Data used in this study are primary data and secondary data. Data collection methods used were observation ,interview sarein-depth interviews and documentation. Analysis of the data used by thein teractive model of the Sugiyono Milles and Huberman, 2012:337: (1) data collection, (2) data reduction, (3) presentation of data, (4) conclusion.The results ofthis study concluded that the reason for the blue awning owners to maintain their business in the village of Olo Marapak Koto Padang West that is 1). Large revenues, 2).It does not takes kill, 3). The use of are latively short time, 4).Venture capitalis not too large, 5). Sanctions in light of the authorities.